Characterization of Chenin Blanc wines produced by natural fermentation and skin contact : focus on application of rapid sensory profiling methods - Weightman, Jayne (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2014.